High-Density Substrate Mapping in Brugada Syndrome: Combined Role of Conduction and Repolarization Heterogeneities in Arrhythmogenesis - Lambiase, P.D.; Ahmed, A.K.; Ciaccio, E.J.; Brugada, R.; Lizotte, E.; Chaubey, S.; Ben-Simon, Ron; Chow, A.W.; Lowe, M.D.; McKenna, W.J. (Circulation (New York, N.Y.), 2009)
Background— Two principal mechanisms are thought to be responsible for Brugada syndrome (BS): (1) right ventricular (RV) conduction delay and (2) RV subepicardial action potential shortening. This in vivo high-density mapping study evaluated the conduction and repolarization properties of the RV in BS subjects. Methods and Results— A noncontact mapping array was positioned in the RV of 18 BS patients and 20 controls. Using a standard S 1 -S 2 protocol, restitution curves of local activation time and activation recovery interval were constructed to determine local maximal restitution slopes. Significant regional conduction delays in the anterolateral free wall of the RV outflow tract of BS patients were identified. The mean increase in delay was 3-fold greater in this region than in control ( P =0<0.001). Local activation gradient was also maximally reduced in this area: 0.33±0.1 (mean±SD) mm/ms in BS patients versus 0.51±0.15 mm/ms in controls ( P <0.0005). The uniformity of wavefront propagation as measured by the square of the correlation coefficient, r 2 , was greater in BS patients versus controls (0.94±0.04 versus 0.89±0.09 [mean±SD]; P <0.05). The odds ratio of BS hearts having any RV segment with maximal restitution slope >1 was 3.86 versus controls. Five episodes of provoked ventricular tachycardia arose from wave breaks originating from RV outflow tract slow-conduction zones in 5 BS patients. Conclusions— Marked regional endocardial conduction delay and heterogeneities in repolarization exist in BS. Wave break in areas of maximal conduction delay appears to be critical in the initiation and maintenance of ventricular tachycardia. These data indicate that further studies of mapping BS to identify slow-conduction zones should be considered to determine their role in spontaneous ventricular arrhythmias.